Comparative analyses of metabolic fingerprint integrated with cytotoxic activity and in silico approaches of the leaves extract of Spondias mombin L. and Spondias tuberosa Arr. Cam. from Northeast, Brazil - Guedes, Jhonyson Arruda Carvalho; Santiago, Yuri Gomes; dos Reis Luz, Licia; Silva, Maria Francilene Souza; Ramires, Christiane Mendes Cassimiro; de Lima, Maria Auxiliadora Coelho; de Oliveira, Viseldo Ribeiro; do Ó Pessoa, Cláudia; Canuto, Kirley Marques; de Brito, Edy Souza; F. Lima, Marcelo [UNESP]; Alves, Ricardo Elesbão; et al. (Elsevier, 2020)
Spondias species are a relevant source of natural-bioactive compounds in Brazilian folk medicine, and its biological potential has not been explored. Thus, this study aimed to determine the metabolomic fingerprint of Spondias mombin and Spondias tuberosa leaves based on the use of reversed-phase liquid chromatography coupled to a high-resolution mass spectrometer (UPLC-HRMS). The analysis by UPLC-HRMS allowed the annotation of 31 metabolites. The multivariate analysis allowed us to identify the biomarkers responsible for the distinction between species. Also, we correlate the biomarkers of S. mombin and S. tuberosa as supposed responsible for the difference in the degree of cytotoxicity between them. The in silico evaluation was performed to give more consistency to the correlation between biomarkers and cytotoxicity, which were compared to commercial drugs. Therefore, this study showed that S. mombin has the potential to become an input for the pharmaceutical industry as a source of raw material that can positively impact the sectors of agricultural production.
Keywords: Chemometrics; High-resolution mass spectrometry; Liquid chromatography; Metabolomics; Umbu; Yellow mombin